141k views
2 votes
write an expression that is equivalent to 7 3/4 + 1 3/4 - 3 5/6 that uses addition instead of subtraction

User Harijay
by
4.8k points

1 Answer

3 votes

Answer:

7 3/4 + 1 3/4 - 3 5/6 = 4 + 3/4 + 3/4 + 1/6

Explanation:

7 3/4 + 1 3/4 - 3 5/6

we do not want the minus sign.

7 3/4 + 1 3/4 - 3 5/6 = 7 3/4 + 1 3/4 - 3 - 5/6

7 3/4 + 1 3/4 - 3 5/6 = 7+ 3/4 + 1 + 3/4 - 3 - 5/6

7 3/4 + 1 3/4 - 3 5/6 = 7 + 1 - 3 + 3/4 + 3/4 - 5/6

7 3/4 + 1 3/4 - 3 5/6 = 5 + 3/4 + 3/4 - 5/6

7 3/4 + 1 3/4 - 3 5/6 = 4 + 3/4 + 3/4 + 1 - 5/6

7 3/4 + 1 3/4 - 3 5/6 = 4 + 3/4 + 3/4 + 1/6

User Maarten Wolfsen
by
4.6k points